2007
DOI: 10.1007/s00018-007-6543-y
|View full text |Cite
|
Sign up to set email alerts
|

Drugs of the future: the hormone relaxin

Abstract: The peptide hormone relaxin is emerging as a multi-functional factor in a broad range of target tissues including several non-reproductive organs, in addition to its historical role as a hormone of pregnancy. This review discusses the evidence that collectively demonstrates the many diverse and vital roles of relaxin: the homeostatic role of endogenous relaxin in mammalian pregnancy and ageing; its gender-related effects; the therapeutic effects of relaxin in the treatment of fibrosis, inflammation, cardioprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
78
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 146 publications
(190 reference statements)
0
78
0
Order By: Relevance
“…In recent studies, we and others have consistently shown that serelaxin is a potent antifibrotic in a wide variety of experimental models and scenarios. [7][8][9][10][11]13,14,[16][17][18][19] Although these studies are important proof of principle, preclinical validation requires a number of additional steps including head-to-head comparison with standard care and validation of therapeutic rather than preventative strategies. These issues are specifically addressed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, we and others have consistently shown that serelaxin is a potent antifibrotic in a wide variety of experimental models and scenarios. [7][8][9][10][11]13,14,[16][17][18][19] Although these studies are important proof of principle, preclinical validation requires a number of additional steps including head-to-head comparison with standard care and validation of therapeutic rather than preventative strategies. These issues are specifically addressed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Furthermore, it can ameliorate fibrosis in multiple organs undergoing simultaneous aberrant matrix/collagen accumulation. 11 The collagen-inhibitory actions of relaxin are mediated by its ability to promote nitric oxide-mediated inhibition of Smad2 phosphorylation (pSmad2; an intracellular protein that promotes transforming growth factor [TGF]-β1 signal transduction) 12 and hence the profibrotic actions of TGF-β1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, serelaxin (RLX), the recombinant molecule corresponding to the human hormone relaxin-2 (Hossain and Wade, 2014), emerges as a feasible candidate. RLX, best known for its effects on reproduction (Sherwood, 2004), also exhibits anti-inflammatory and antifibrotic properties (Masini et al, 2004;Samuel et al, 2007;Bonacchi et al, 2009). In a setting of allergic airway disease, RLX has been shown to inhibit infiltration of proinflammatory cells into the lung and adverse airway remodeling (Bani et al, 1997;Royce et al, 2009Royce et al, , 2014, promote dilation of alveolar blood capillaries, and reduce the thickness of the air-blood barrier (Bani et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Gene targeting experiments in mice resulted in viable Rln1 and Rxfp1-deficient animals (5-7). Detailed analysis of their phenotype revealed an involvement of this peptide in extracellular matrix remodeling; a fibrosis development was described in various Rln1-or Rxfp1-deficient organs (8). The role of relaxin in regulation of angiogenesis and vasodilation was linked to the induction of vascular endothelial growth factor, up-regulation of nitric oxide synthase, matrix metalloproteases and other factors (9).…”
Section: Introductionmentioning
confidence: 99%